Normalized COVID-19 prevention and control management - Yu Ren; Hua Luo (Journal of Family Medicine and Primary Care, 2022)
When the coronavirus disease (COVID-19) virus swept the world in December 2019, it brought widespread side-effects. While there is no specific treatment for COVID-19, individuals and collectives often respond rapidly to develop a routine, making the prevention and control of COVID-19 normalized and institutionalized and creating vaccines successfully in a short time. However, this situation also exposed a spectrum of problems triggered by lockdown, isolation, and vaccinations. Herein, we analyze the prevention management of COVID-19 from epidemic psychology in order to provide a new sight for overcoming the psychological problems of COVID-19.